PERLINDUNGAN HUKUM TERHADAP HAK-HAK TENAGA KERJA YANG DI-PHK : STUDI PADA PABRIK GULA (P.G) JATIBARANG-BREBES - Irma Maulida (Hukum Responsif, 2016)
Namely the recognition of legal protection and guarantees provided by the law in relation to human rights. Legal protection of the rights of workers who were laid off to discuss the rights of labor after being laid off. In the implementation of the legal protection of the rights of workers are laid off must be in accordance with applicable regulations, namely the Employment Act No. 13 of 2003 on Labour, Kep. 150 / Men / 2000 regarding the determination of separation, gratuity and compensation. Issues examined in this study are: 1. How is the implementation of the legal protection of the rights granted by employers on workers who had been fired at the Sugar Factory Jatibarang-Brebes? 2. How did the factors that affect the protection of the law of the rights of workers who were laid off as well as a way to resolve the Sugar Factory Jatibarang-Brebes ?. The method used in this study is the use of qualitative methods of descriptive data in the form of words written or spoken of behavior observed. While the objectivity and validity of the data by comparing the data obtained from the study were analyzed interactively from dsata collection, data reduction, data presentation to conclusion. Keywords: Legal Protection, Rights of Labor, layoffs